The effects of artificial light at night (ALAN) on the circadian biology of marine animals - Stanton, Daniel L.; Cowart, Jonathan R. (Frontiers in Marine Science, 2024)
The effects of anthropogenic sources of light on the circadian biology of marine animals are largely unexplored at the molecular and cellular level. Given that light is a major driver of circadian rhythms at the behavioral, physiological, cellular, and even molecular levels, it is important to consider the effects that anthropogenic light, especially at night, has on aquatic species. With the expanding data generated from circadian clock research, it is surprising that these techniques have not been applied more frequently to better understand how artificial light affects animal circadian rhythms. Circadian research has been limited to behavioral and physiological observations in wild marine animals rather than a cellular and molecular understanding due to the logistical constraints. While there are some benefits to using artificial light at night (ALAN), there have also been many studies reporting physiological and behavioral consequences in response to exposure to ALAN. Here, the benefits and consequences of using ALAN in the marine environment are reviewed. Furthermore, perspectives on research limitations and future research directions are discussed. Taken together, this is an important area in which more information is required to translate our understanding of circadian biology into better practices to promote the health and welfare of marine animals.